2017
DOI: 10.1038/emi.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells release microparticles containing human argonaute 2 and miRNAs to target genes of Plasmodium falciparum

Abstract: Red blood cells (RBCs) are known to function as a refuge for providing food resources and as a shelter against the host’s immune system after malaria parasite (Plasmodium) infection. Recent studies have reported significant production of extracellular vesicles (microparticles, MPs) in the circulation of malaria patients. However, it is unclear how these extracellular vesicles are generated and what their biological functions are. In this study, we isolated the MPs from a culture medium of normal RBCs and malar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 53 publications
3
70
0
Order By: Relevance
“…MiRNAs, human Argonaute protein and RISC complex could be detected in the parasites [40] as well as in EVs released by infected erythrocytes [44,45]. EVs carried Argonaut-miRNAs complex affecting recipient cells that have been demonstrated to alter vascular function [44] or parasite's var gene expression [46]. These studies strengthen the roles of EVs-derived miRNAs in malaria pathogenesis.…”
Section: Introductionmentioning
confidence: 53%
“…MiRNAs, human Argonaute protein and RISC complex could be detected in the parasites [40] as well as in EVs released by infected erythrocytes [44,45]. EVs carried Argonaut-miRNAs complex affecting recipient cells that have been demonstrated to alter vascular function [44] or parasite's var gene expression [46]. These studies strengthen the roles of EVs-derived miRNAs in malaria pathogenesis.…”
Section: Introductionmentioning
confidence: 53%
“…Chamnanchanunt et al found that hsa-miR-451a was down-regulated in P. vivax-infected patient plasma [44]. Other studies demonstrated that EVs cargo hsa-miR-451a could be internalized to target the parasites and diminish the parasite burden [38,43]. Furthermore, in an in vitro study, red blood cell derived EVs containing hsa-miR-451a and human argonaute 2 (Ago2) were shown to be internalized by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…By studying the EV compartment as a whole the chances of nding differences in miRNA expression between the groups would be increased. Five miRNA were selected based on previous in vitro, animal model, or clinical studies that suggested these miRNAs had a potential involvement in malaria, namely: hsa-miR-451a, hsa-miR-150-5p, hsa-miR-15b-5p, hsa-let-7a, and hsa-miR-16-5p [37][38][39][41][42][43][44]48]. This study provides novel insight about circulating EVs-derived miRNAs in human malaria.…”
mentioning
confidence: 99%
“…Subsequent to infection with malaria parasites, iRBCs secrete significantly more extracellular vesicles than uninfected cells (Mantel et al, 2016; Regev-Rudzki et al, 2013). Extracellular vesicles derived from iRBCs contain many factors, including antigens, virulence factors, mammalian-and parasite-derived nucleic acids, and the RNAi machinery (Babatunde et al, 2018;Mantel et al, 2016;Sampaio et al, 2018;Wang et al, 2017).…”
Section: Extracellular Vesicles and Arthropod-borne Microbial Transmimentioning
confidence: 99%